Public perception of urban identity in post-Soviet city: the case of Vinnytsia, Ukraine - Melnychuk, Anatoliy; Gnatiuk, Oleksiy (Hungarian Geographical Bulletin, 2019)
This study deals with urban identity in Vinnytsia, one of the most economically vibrant Ukrainian cities, arguably known as a fiefdom of key Ukrainian power holders since the Euromaidan. Assuming that urban space may be treated simultaneously as a mirror and a factor of urban identity, the authors tried to look at urban identity under the lens of urban space transformations. The sociological survey conducted in 2016 and covering 168 respondents was focused on public representations about the city in whole and particular places in the city as well, including important recent changes of urban landscape. We came to conclusion that Vinnytsia represents an inclusive model of urban identity growing from additional actualized strata of historical memory. However, there is a stable core of identity, requiring a great deal of effort to be changed. We confirmed our hypothesis that identity-related discussions in Vinnytsia are centred on the issue of leadership, caused by current privileged position of the city and successful municipal reforms implemented by the local administration, and the issue of modernization, including aggressive commercialization, threating the historic urban landscape. The survey revealed the re-assessment of the role of industry as an element of local identity and demonstrated that the public requirements to the urban space experienced a strong shift towards human-friendliness, aesthetics, safety and diversity instead of political or ideological symbols. We observed pronounced shift to the local and regional values, although the connection with the national identity remains important. Finally, we came to conclusion that the success of transformation is largely defined by the possibility to painlessly combine new senses and connotations of places with the already existing. Thus, local identity may be considered as one of the key factors determining the perception of the urban space transformation, making urban landscape more resilient to the possible harmful impendences.